Seismic fragility analysis of critical facilities in communication base station based on shaking table test. (April 2023) - Feng, Lifei; Yang, Hanwen; Chenxi, Mao; Ou, Jinping
Abstract: The seismic fragility analysis of communication equipment can be utilized for pre-earthquake disaster prediction and targeted improvement of their seismic performance; on the other hand, it can also serve as a basis for post-earthquake loss estimation. However, the failure modes of the critical facilities in the base station cannot be accurately predicted by performing finite element analysis. Therefore, this paper conducts the seismic fragility analysis for storage battery pack (SBP) and equipment cabinet (EC), commonly used in communication base stations, through the incremental dynamic analysis method based on the shaking table test. A total of two SBPs and three ECs with the same specification were included in this study. The seismic ground records were processed using amplitude modulation before being input into the shaking table for testing. Test phenomena were used to determine the damage level and damage index for SBP and EC. Based on the results of the incremental dynamic analysis of the shaking table test, the seismic fragility of the SBP and EC was assessed. It was found that the failure of SBP was due mainly to the collisions of storage batteries, while that of EC was caused primarily by excessive displacement response. The findings of this paper will contribute to the evaluation of the seismic performance of the overall communication system.